Clinical Impact and Emerging Multi Drug Resistance of Acinetobacter Baumannii and Pseudomonas Aeruginosa Isolates - Shah, Manali Hitenbhai; Vaghela, Geeta Mukesh (Annals of Pathology and Laboratory Medicine, 2018)
Background: Acinetobacter and Pseudomonas are the two most important member of the Non fermenter group. They cause serious life threatening infections. They are mainly nosocomial causing infection in deprived immunity. Multi drug resistance is the major problem which may be intrinsic, or extrinsic. Methods: It was a prospective study done in tertiary care hospital, Surat. All clinical samples were included. Processing of samples, identification of isolates and antibiotic susceptibility were done using standard guidelines. Clinical correlation of the patients was done. Result: Total 151 samples showed growth of Acinetobacter and Pseudomonas. A. Baumannii was the most common isolated followed by P. aeruginosa. Only Polymyxins showed complete sensitivity. Most of the isolates were from surgical and orthopedic wards with trauma as predominant infectious cause. Monomicrobial infections and male preponderance were observed. Most of the patients got discharged within 10 days of admission. Clinical outcome showed 72 % of discharge rate followed by death. Conclusion: The only group having complete sensitivity towards organisms was the Polymyxin group. The most common cause being trauma, strict infection control practices with emphasis on hand hygiene should be followed to prevent emergence of pan drug resistant bacteria.